Protective Effects of Cannabidiol on Chemotherapy-Induced Oral Mucositis via the Nrf2/Keap1/ARE Signaling Pathways. (25th May 2022) - Li, Lin; Xuan, Yaowei; Zhu, Biao; Wang, Xing; Tian, Xiaoyu; Zhao, Lisheng; Wang, Yan; Jiang, Xiaoxia; Wen, Ning
Abstract : Oral mucositis (OM) is a common complication during chemotherapy characterized by ulceration, mucosa atrophy, and necrosis, which seriously interferes with nutritional intake and oncotherapy procedures among patients. However, the efficacy of current treatments for OM remains limited. Cannabidiol (CBD) is a natural cannabinoid with multiple biological activities, including antioxidant and anti-inflammatory potential. In this study, we aimed to investigate the chemopreventive effects and mechanisms of CBD in protecting C57BL/6N mice and human oral keratinocytes (HOK) from 5-fluorouracil- (5-FU-) induced OM. Here, we found that CBD alleviated the severity of 5-FU-induced OM in mice, including improved survival, decreased body weight loss, reduced ulcer sizes, and improved clinical scores. Histologically, CBD restored epithelial thickness and normal structure in tongue tissues. Meanwhile, CBD attenuated reactive oxygen species (ROS) overproduction and improved the antioxidant response, suppressed the inflammatory response, promoted the proliferation of epithelial cells, and inhibited 5-FU-induced apoptosis. In vitro, consistent outcomes showed that CBD suppressed cellular ROS levels, enhanced antioxidant ability, reduced inflammatory response, promoted proliferation, and inhibited apoptosis in 5-FU-treated HOK cells. In particular, CBD upregulated the expression levels of antioxidant enzymes, heme oxygenase-1 (HO-1) and NAD(P)H quinine oxidoreductase 1 (NQO1), by increasing the expression and nuclear translocation of nuclear factor erythroid 2-related factor 2 (Nrf2) and decreasing Kelch-like ECH-associated protein 1 (Keap1). Notably, the Nrf2 inhibitor ML385 reversed the protective effect of CBD. Nrf2-siRNA transfection also significantly blunted the antioxidant effect of CBD in in vitro OM model. Collectively, our findings suggested that CBD protected against 5-FU-induced OM injury at least partially via the Nrf2/Keap1/ARE signaling pathways, highlighting the therapeutic prospects of CBD as a novel strategy for chemotherapy-induced OM.